2013
DOI: 10.5653/cerm.2013.40.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation and liver dysfunction: Is a clinical relationship possible? A case of hepatic failure after repeated cycles of ovarian stimulation

Abstract: Liver damage induced by ovarian stimulation has been demonstrated in some cases reported in the literature. However, there has never been a fruitful debate on this topic. The present manuscript tried to fill this gap. We reported a case of a 35-year-old nulliparous woman admitted to our obstetric emergency room for severe pre-eclampsia. She had been subjected to four cycles of controlled ovarian stimulation for intrauterine insemination. At 32 weeks of gestation, she developed severe pre-eclampsia, which led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…18 Excessive ovarian stimulation may increase the risk of liver failure later in pregnancy, particularly as IVF is associated with increased risk of hypertensive disorders of pregnancy, for example haemolysis, elevated liver enzymes, and low platelet syndrome (HELLP). 19 In LT recipients, a few reports exist of successful IVF outcomes. [20][21][22][23] In this report, we describe the outcomes and impact of IVF in a range of presentations of liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…18 Excessive ovarian stimulation may increase the risk of liver failure later in pregnancy, particularly as IVF is associated with increased risk of hypertensive disorders of pregnancy, for example haemolysis, elevated liver enzymes, and low platelet syndrome (HELLP). 19 In LT recipients, a few reports exist of successful IVF outcomes. [20][21][22][23] In this report, we describe the outcomes and impact of IVF in a range of presentations of liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance for the measurements of the liver enzymes is of critical value to evaluate the effect of the treatments on general health. The previous reports indicated that repeated ovarian stimulation might deteriorate the hepatic functions, leading to liver failure [44]. There have been variations in ALT and AST activities due to animal physiological status.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small number of reported cases, it seems that ICP recurrence during third trimester might be possible when it has already been developed during the first trimester, probably because during the third trimester estrogen levels rise again [ 37 ] and these women have a predisposition for ICP development [ 38 ]. ICP is associated with adverse pregnancy and perinatal outcomes such as preterm labor, fetal asphyxia, meconium-stained amniotic fluid, and stillbirth and with an increased risk of preeclampsia, especially among women with an early ICP manifestation and twin gestations [ 39 ].…”
Section: Discussionmentioning
confidence: 99%